Calcium Soap Production from PFAD Using Ca(OH)2 as Calcium Source for Animal Feed - Gusti Al Hakim - Nim: 13013039, Maulana
Palm fatty acid distillate (PFAD) is a by-product of the crude palm oil (CPO) refining process. In some countries such as the UK and America, PFAD is used as raw materials for the production of ruminant fat supplements in the form of calcium soap. As the largest palm oil producer in the world, Indonesia has not utilized PFAD to the optimum, so this product is not processed and only exported. In addition, calcium soap as a fat supplement proved beneficial to increase milk production of dairy cows. This study aims to determine the reactant stoichiometric mole ratio and water temperature that produce the best quality of calcium soap. The stoichiometric mole ratio of the reactants used is 1; 1.5; 2; 2.5 and 3. Water temperature used is 60, 70, and 80˚C. All variations of the saponification reaction were carried out using modified fusion method. Analysis performed on the calcium soap is the acid value, ash content, and moisture content. Based on the literature review, the appropriate method for making calcium soap is a modified fusion method. Analysis of the acid value shows the higher the reactant stoichiometric mole ratio, the lower the acid value. The highest conversion resulting in the water temperature of 60Ã‚Â°C. Analysis of ash content shows the higher the reactant stoichiometric mole ratio, the higher the ash content of the soap. The reactant stoichiometric mole ratio that yielding calcium soap with ash content below the cow's absorption limit is 1 and 1.5. Water temperature does not affect the ash content of calcium soap. The moisture content analysis showed that the higher the stoichiometric mole ratio of the reactants, the lower the moisture content.